IMPLEMENTASI PROGRAM BACA TULIS AL-QUR’AN (BTQ) DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN KELAS II B DI SDS IT SULTHONIYAH SAMBAS TAHUN PELAJARAN 2022-2023 - Yusnani (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2024)
This thesis discusses the implementation of the Al-Qur’an reading and writing (BTQ) program in improving the ability to read the Al-Qur’an for class II B at SDS IT Sulthoniyah Sambas for the 2022-2023 academic year. The researcher has three objectives, including the following: first, to find out the concept of the Al-Qur’an Reading and Writing (BTQ) program in improving the ability to read the Al-Qur’an for class II B at SDS IT Shulthoniyah Sambas for the 2022-2023 academic year. Second, to find out the implementation of the BTQ program in improving the ability to read the Al-Qur’an for class II B at SDS IT Sulthoniyah Sambas for the 2022-2023 academic year. Third, to find out the learning outcomus of the BTQ program in improving the ability to read the Al-Qur’an for class II B at SDS IT Sulthoniyah Sambas for the 2022-2023 academic year. This research uses a qualitative approach and phenomenological type of research. Data collection techniques in this study include observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and conclusions. The technique of checking the validity of data uses triangulation and member check. The results showed that: The concept of the BTQ program in improving the ability to read the Qur'an class II B is reading the Qur'an, writing hijaiyyah letters, memorizing hadiths, practicing Arabic conversations, and memorizing asmaulhusna. The implementation of the BTQ program in improving the ability to read the Qur'an class II B is reading and writing the Qur'an (BTQ) carried out three days a week, the method used is the tasmi method, and the evaluation is carried out directly The learning outcomes of the BTQ program in improving the ability to read the Qur'an class II B are quite good where there are already some grade II B students who continue to the big Qur'an or juice. Students who have not advanced to juice have also many Iqra' 4, 5, and 6.